Faithful and fearful: does religion promote or reduce fear of crime in Germany? - Steinmann, Jan-Philip (European journal of criminology, 2024)
This article complements existing victimological studies on religion by investigating whether religion promotes or reduces fear of crime in Germany. According to the generalized insecurity approach and the theory of social production functions, religion and fear of crime are linked via secularization-induced diffuse insecurities. It is expected that different facets of religion are tied to fearing crime in different ways because the projection of secularization-induced diffuse insecurities occurs only among those individuals whose religious capital is devaluated. Empirical analyses of data from the 2021 German General Social Survey reveal that some religious minority groups are particularly likely to fear crime, religious belief is positively related to fearing crime, and religious behavior is negatively associated with fearing crime. Additionally, religion can promote fear of crime equally in East and West Germany. In conclusion, the study emphasizes the significance of religion in relation to the fear of crime and underscores the benefits of a general theoretical approach.